Intelligent control station for improved quality management in flat steel production*. Issue 20 (2016) - Colla, V.; Nastasi, G.; Maddaloni, A.; Holzknecht, N.; Heckenthaler, T.; Hartmann, G.
Abstract: Reaching the maximum yield of produced stainless flat products is an important aim to be successful in the competitive market. This paper describes a solution to optimise the allocation of orders to coils taking into account the actual product quality as well as the quality expected by the customer. In opposite to already available solutions also the appearance of over-quality products is taken into account. Especially for high quality stainless flat products the re-allocation of over-quality products to orders with higher demands can increase the added value distinctly. Another topic is the processing of Manufacturing Specifications (MS). A concept for the digitization of usually freely formulated MS is presented as well as a systematic monitoring, if the MS are really considered by the plant operators. The shown use cases were implemented at the German sites of Outokumpu Oyj, the Finnish producer of stainless flat products sited in Espoo.